Information and knowledge management in public sector networks: the case of the US intelligence community - Desouza, Kevin C. (2009)
This article contributes to the public management literature by exploring the critical challenges that underpin the construction of robust information and knowledge management strategies in networked settings. the ability of the network to sustain itself, thrive, and achieve its objectives depends on the success that the network has in organizing and coordinating its constituent organizations. The network's collaborative information and knowledge management strategy is critical to the functioning of the network and the achievement of objectives. A robust information and knowledge management strategy will bring organizations in the network together, help them share resources, collaborate on efforts, and further objectives in a holistic manner. An inadequate information and knowledge management strategy might lead to disconnects in organizations due to lack of information sharing, poor collaborative knowledge generation, lack of coordination, leading to a fragmented network. Drawing on a multi-year, multi-method, and multi-organization study of the United States Intelligence Community (USIC), the article puts forth a comprehensive framework to examine information and knowledge management challenges within the USIC, as well as other public sector organizations. - Reproduced.
Keywords: Knowledge management; Public administration